Indonesian Non-English Major Learners’ Attitudes toward Instagram to Practice Speaking in English: A Survey Study - Damaryanan, Rama Elrianto; Subekti, Adaninggar Septi (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2024)
Speaking skill is often considered one of the most challenging skills for learners, perhaps due to the trial and error nature of speaking shunning shy and unconfident second/foreign language (L2) learners of English. In the meantime, Instagram raises as one of the most popular social media platforms among the young generation, including L2 learners. Hence, the present study aimed to investigate non-English major learners’ attitudes toward the use of Instagram to practice speaking in English. This study involved 102 Indonesian active Instagram user learner participants across Indonesia in an online survey. Through descriptive statistics on SPSS 25, the study found that the participants generally had positive attitudes towards the use of Instagram to practice speaking in English. Nonetheless, even though they considered Instagram a good platform to practice speaking, they were slightly less motivated to actually use it for learning purposes. These findings call for teachers to channel the popularity of Instagram among learners and their familiarity with it for L2 learning purposes through class instruction.